2020
DOI: 10.1093/wbro/lkaa004
|View full text |Cite
|
Sign up to set email alerts
|

Can Jobs Programs Build Peace?

Abstract: In the last decade, well over $10 billion has been spent on employment programs designed to contribute to peace and stability. Despite the outlay, whether these programs perform, and how they do so, remain open questions. This study conducts three reviews to derive the status quo of knowledge. First, it draws on academic literature on the microfoundations of instability to distill testable theories of how employment programs could affect stability at the micro level. Second, it analyses academic and grey liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In particular, the program made refugees in the treatment group more optimistic, left them feeling more capable to meet their current needs and has resulted in a reduction of relative group bias in the dictator game. These social outcomes appear to be driven by a direct "program effect" as identified by Brück et al (2021) as opposed to an indirect effect via employment gains. For these specific outcomes, we imagine, simply, that involvement in the program sent a positive signal to refugee participants about their future competitiveness in the labor market, which improved optimism.…”
Section: Impact Of Treatment On Group-based Biasesmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, the program made refugees in the treatment group more optimistic, left them feeling more capable to meet their current needs and has resulted in a reduction of relative group bias in the dictator game. These social outcomes appear to be driven by a direct "program effect" as identified by Brück et al (2021) as opposed to an indirect effect via employment gains. For these specific outcomes, we imagine, simply, that involvement in the program sent a positive signal to refugee participants about their future competitiveness in the labor market, which improved optimism.…”
Section: Impact Of Treatment On Group-based Biasesmentioning
confidence: 98%
“…The question of whether jobs programs, as opposed to having a job, alleviate societal tensions has limited and mixed evidence (Brück et al, 2021). For one, jobs programs in fragile environments have shown limited results, largely due to labor market demand constraints (Blattman and Ralston, 2015).…”
Section: Theoretical Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main theoretical framework used here when discussing conflict and peace is that they revolve around three key areas: opportunity, grievance, and contact (Brück et al 2021). A report supported by the International Labour Organization (ILO), Peacebuilding Support Office (PBSO), the United Nations Development Programme (UNDP), and the World Bank Group (WBG) which examines the literature and aid interventions suggests that most are predicated on the idea that creating opportunities, reducing grievance, and creating contact (and through contact, understanding) between communities are all plausible routes to reducing support for violence (Brück et al 2016).…”
Section: Peacementioning
confidence: 99%
“…Providing youth with jobs may not be enough to promote social cohesion. A 2015 study by Mercy Corps found that "experiences of injustices" were a driving factor in Afghan youths' feeling disaffected by the government (Mercy Corps 2015, see also Brück et al 2019). Perceived social inequalities are bad for social cohesion, and people are less likely to view decision-making institutions as legitimate if they feel systematically excluded from them on the matters affecting their lives (World Bank 2013c).…”
Section: Relevance To Well-being and Social Cohesionmentioning
confidence: 99%